2015
DOI: 10.1007/s10900-015-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Rural Family Perspectives and Experiences with Early Infant Hearing Detection and Intervention: A Qualitative Study

Abstract: Infant hearing loss has the potential to cause significant communication impairment. Timely diagnosis and intervention is essential to preventing permanent deficits. Many infants from rural regions are delayed in diagnosis and treatment of hearing loss. The purpose of this study is to characterize the barriers in timely infant hearing healthcare for rural families following newborn newborn hearing screening (NHS) testing. Using stratified purposeful sampling, the study design involved semi-structured phone int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 15 publications
7
52
0
Order By: Relevance
“…44 Misinformation from providers and difficulty coordinating appointments were prominent barriers to appropriate follow-up for infant hearing testing. 45 …”
Section: Barriers To Pediatric Hearing Healthcare Deliverymentioning
confidence: 99%
“…44 Misinformation from providers and difficulty coordinating appointments were prominent barriers to appropriate follow-up for infant hearing testing. 45 …”
Section: Barriers To Pediatric Hearing Healthcare Deliverymentioning
confidence: 99%
“…Misinformation, inconsistent care, cultural or health beliefs, socioeconomic status, mistrust of the healthcare system, and lack of social support influence nonadherence within healthcare . Within the EHDI field, factors complicating access to care include poor communication of hearing screening results, difficulty in obtaining outpatient testing, inconsistencies in healthcare information from primary care providers, lack of local resources, insurance‐related healthcare delays, and conflicts with family and work responsibilities . Addressing these barriers to care is complicated and may require multiple approaches.…”
Section: Discussionmentioning
confidence: 99%
“…25 Within the EHDI field, factors complicating access to care include poor communication of hearing screening results, difficulty in obtaining outpatient testing, inconsistencies in healthcare information from primary care providers, lack of local resources, insurancerelated healthcare delays, and conflicts with family and work responsibilities. 38 Addressing these barriers to care is complicated and may require multiple approaches. Families of children with hearing loss report that they lack confidence and resources needed for healthcare decision making for their child.…”
Section: Discussionmentioning
confidence: 99%
“…The available studies on this topic focused mainly on how parents value the access to diagnosis and early intervention [9,10], to early literacy [11], or to the mainstream schools through the adequate provision of educational services [12]. From these studies, it can be highlighted that DHH children and their families are still facing important obstacles to access the necessary services, such as: important delays in the first diagnosis and treatment of hearing loss [9]; poor communication of hearing screening results, inconsistencies in healthcare information from primary care providers, and lack of local resources [10]; an inadequate access to literacy during preschool activities [11]; or a lack of collaboration with special educator in mainstream schools [12].…”
Section: The Access To Services and Supports Of Deaf And Hard-of-hearmentioning
confidence: 99%
“…In many cases, although services were available, they remained elusive for parents who lived in remote areas. As research has shown [9,10], living in a rural or remote geographical locations limits the access to social and health services and put families at risk. There are models of hearing-health care for children who live with their families in remote areas where services are found to be cost effective.…”
Section: Bringing and Adapting The Services To The Rural Settingsmentioning
confidence: 99%